2009
DOI: 10.1007/s12033-009-9187-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression and Optimized Production of an Aspergillus aculeatus Endo-1,4-β-mannanase in Yarrowia lipolytica

Abstract: The Aspergillus aculeatus MRC11624 man1 gene, encoding an endo-beta-1,4-mannanase, was cloned and expressed in the promising heterologous enzyme producer, the ascomycetous yeast Yarrowia lipolytica. Both single- and multi-copy transformants were constructed, and the secretion of the enzyme was evaluated as an in-frame fusion with the LIP2 secretion signal, as well as with its natural secretion signal. In shake-flask analysis, the highest volumetric enzyme activity (13,073 nkat/ml) and specific enzyme activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…Several examples of ␤-mannanase production in excess of 1 g/l through heterologous expression in fungal systems have been reported (see Table 1), both for the expression of fungal genes [66][67][68] and for expression of a bacterial B. subtilis ␤-mannanase in Pichia pastoris [69]. Expression of the Aspergillus aculeatus man1 gene in Yarrowia lipolytica and cultivation of the recombinant strain in fed batch culture has resulted in 5.9 g/l enzyme (1575 U/ml), the highest levels reported to date for a fungal or bacterial ␤-mannanase.…”
Section: Heterologous Production Of ␤-Mannanasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several examples of ␤-mannanase production in excess of 1 g/l through heterologous expression in fungal systems have been reported (see Table 1), both for the expression of fungal genes [66][67][68] and for expression of a bacterial B. subtilis ␤-mannanase in Pichia pastoris [69]. Expression of the Aspergillus aculeatus man1 gene in Yarrowia lipolytica and cultivation of the recombinant strain in fed batch culture has resulted in 5.9 g/l enzyme (1575 U/ml), the highest levels reported to date for a fungal or bacterial ␤-mannanase.…”
Section: Heterologous Production Of ␤-Mannanasesmentioning
confidence: 99%
“…Expression of the Aspergillus aculeatus man1 gene in Yarrowia lipolytica and cultivation of the recombinant strain in fed batch culture has resulted in 5.9 g/l enzyme (1575 U/ml), the highest levels reported to date for a fungal or bacterial ␤-mannanase. Such production levels are partly due to high biomass densities attainable with the Y. lipolytica yeast expression system, which is a considerable advantage compared to the use of filamentous fungi such as A. niger [67,68]. ␤-Mannanase with a purity of up to 97% in the culture supernatant has been obtained by heterologous expression in P. pastoris [70], requiring little or no further purification prior to industrial application.…”
Section: Heterologous Production Of ␤-Mannanasesmentioning
confidence: 99%
“…P13 (Zhao et al 2010), Bispora sp. MEY-1 (Luo et al 2009), A. sulphureus MAFIC001 (Chen et al 2007), A. niger BK01 (Cuong et al 2009), A. aculeatus MRC11624 (Roth et al 2009) and Bacillus sp. JAMB-750 (Hatada et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[5] Recombinant protein expression levels in the Y. lipolytica system can also be improved using highcell-density fermentation. Roth et al [28] reported that the enzyme activity of an Aspergillus aculeatus endo-1, 4-bmannanase obtained in Braun C 15 L fermenters was increased by 100% compared to a shake-flask trial. Additionally, Nicaud et al [29] reported a 7.9-fold increase in volumetric lipase activity when produced in fed-batch fermentation compared to batch fermentation.…”
Section: Discussionmentioning
confidence: 99%